(untitled) (International Journal of Business, Economics and Management, 2020)
This study seeks to construct a financial safety index (FSI) for Nigeria. FSI is important for early detection of financial stress and ensures that the financial system is better positioned to reduce the likelihood of financial crisis and negative outcomes on real economic activities. It has capacity to guide policies that are likely to ensure the safety of financial system as well as those that are likely to distort the system. It also has ability of providing support for policy on external economic factors that can affect a country’s financial system. Hence, the developed index incorporates factors that have made significant impacts on Nigeria’s financial system in recent years. It is estimated using principal component analysis (PCA) and some major incidents of systemic pressure were identified from the constructed FSI. The constructed FSI was able to largely capture key macroeconomic trends and developments that shaped the financial industry within the study period. This confirms the relevance of the indicators selected for building the index and implies that the selected indicators played critical roles in the determination of Nigeria’s financial safety. Therefore, the index would assist both the fiscal and monetary policymakers in taking preventive measures against financial instability.